Electrolytic capacitors: design features and problems of the choice - Gurevich, V.I. (Електротехніка і електромеханіка, 2012)
In this paper, the constructions and characteristics of various kinds of electrolytic capacitors are considered. It points out that
often the problems and subsequent damages in electronic equipment are coupled with a wrong choice of electrolytic capacitors.
Recommendations for correct choices of electrolytic capacitors are presented.